2018
DOI: 10.1186/s13256-018-1624-0
|View full text |Cite
|
Sign up to set email alerts
|

An intramural uterine fibroid became submucosal in the puerperium – proposed probable mechanism: a case report

Abstract: BackgroundVaginal prolapse of a large uterine fibroid is a rare phenomenon in a woman who delivered vaginally recently, given that this fibroid might have obstructed labor. The author presents a case report of a vaginally prolapsed large pedunculated submucosal uterine myoma in a woman with a recent uncomplicated vaginal delivery.Case presentationA 25-year-old black African woman had four intramural uterine fibroids of diameters 62 to 94 mm diagnosed in April 2013 with standard ultrasound scan. She got pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Based on these results, one of the possible mechanisms of leiomyoma prolapse is rapid decrease in leiomyoma volume. The rapid reduction of leiomyoma volume also occurs in the post‐partum, and in fact, it has been reported that leiomyoma prolapse occurred in the puerperium 8 . In addition to the cases of literature review, leiomyoma prolapse took place after rapid reduction of leiomyoma volume in our GnRH antagonist case.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Based on these results, one of the possible mechanisms of leiomyoma prolapse is rapid decrease in leiomyoma volume. The rapid reduction of leiomyoma volume also occurs in the post‐partum, and in fact, it has been reported that leiomyoma prolapse occurred in the puerperium 8 . In addition to the cases of literature review, leiomyoma prolapse took place after rapid reduction of leiomyoma volume in our GnRH antagonist case.…”
Section: Discussionsupporting
confidence: 52%
“…The rapid reduction of leiomyoma volume also occurs in the post-partum, and in fact, it has been reported that leiomyoma prolapse occurred in the puerperium. 8 In addition to the cases of literature review, leiomyoma prolapse took place after rapid reduction of leiomyoma volume in our GnRH antagonist case. In the present case, the duration of GnRH antagonist treatment until leiomyoma prolapse was 35 days, which was relatively short compared to all the cases of leiomyoma prolapse during GnRH agonist treatment in the literature review (Table 1).…”
Section: Discussionmentioning
confidence: 66%
“…There are currently no clinical guidelines for treating a pedunculated submucosal myoma during pregnancy or postpartum, as this type of myoma is rare, and there have only been 14 cases reported since 1945, all of which have been accompanied by an occult development of suppuration ( 1 13 ). Sirha et al ( 18 ) have found that surgical intervention combined with more effective antibiotics is the most appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Each article abstract was evaluated, and the relevant original English language articles were read. Relevant articles were cross-referenced to identify related studies or publications on the subject, and cases of transvaginal prolapse of uterine submucous myoma or cervical myoma after delivery since 1949 were summarized ( 1 , 3 – 13 ) ( Table 1 ). The literature review found that transvaginal prolapse of postpartum submucosal fibroids occurred from immediate postpartum to seven weeks postpartum, with 7 of the 14 cases occurring at 4–5 weeks postpartum.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most common complications of leiomyoma are anemia (due to menorrhagia), infertility and miscarriages. 7 Leiomyomas or myomas can either be single, or multiple in numbers and can also differ in perfusion, location and size. Intramural leiomyoma, the most common, develops within the muscular uterine wall.…”
Section: Introductionmentioning
confidence: 99%